2000
DOI: 10.2337/diacare.23.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Serum markers of oxidative stress and severity of diabetic retinopathy.

Abstract: n e t t @ v i s i o n . e r i . h a rv a rd . e d u .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
81
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(93 citation statements)
references
References 7 publications
8
81
1
3
Order By: Relevance
“…In diabetic animals, AGE inhibitors such as aminoguanidine can attenuate the formation of retinal microvascular lesion; however, recent studies indicate that this drug can significantly alleviate diabetic retinopathic lesions without affecting the formation of the AGE pentosidine in retinal basement membrane collagen [89]. This effect might be linked with aminoguanidine's antioxidative property rather than AGE inhibitory properties [90] as oxidative imbalances in diabetic retinopathy have also been extensively reported [91,92]. Interestingly, some studies have reported no significant change of retinal vascular lesions after treatment with antioxidants [93].…”
Section: Age Inhibitors and Prevention Of Retinopathymentioning
confidence: 70%
“…In diabetic animals, AGE inhibitors such as aminoguanidine can attenuate the formation of retinal microvascular lesion; however, recent studies indicate that this drug can significantly alleviate diabetic retinopathic lesions without affecting the formation of the AGE pentosidine in retinal basement membrane collagen [89]. This effect might be linked with aminoguanidine's antioxidative property rather than AGE inhibitory properties [90] as oxidative imbalances in diabetic retinopathy have also been extensively reported [91,92]. Interestingly, some studies have reported no significant change of retinal vascular lesions after treatment with antioxidants [93].…”
Section: Age Inhibitors and Prevention Of Retinopathymentioning
confidence: 70%
“…27 For instance, immunohistochemical analyses have demonstrated enhanced iNOS expression in the retinas of diabetic patients, 23 and both genetic knockout and pharmacological inhibition of iNOS reduce apoptosis in the inner nuclear layer of the avascular retina in ischemic proliferative retinopathy. 28 In addition, NO may act as an angiogenic mediator by stimulating production of VEGF, which has been strongly implicated in the development of proliferative retinopathy. 29,30 In agreement with these observations, we found that iNOS expression was higher in Akita mouse retinas, and HOG-LDL induced an increase in iNOS expression and NO production in human retinal pericytes.…”
Section: Discussionmentioning
confidence: 99%
“…Free iron in its Fe 3+ state will be reduced to Fe 2+ state by various agents like superoxide and ascorbate (12) and glucose induced reduction by NADPH dependent reactions (13). Existence of oxidative stress in diabetes is well proved by numerous studies (14). Previous studies have proved that poor glycemic control causes glycation of proteins and increased oxidative damage of proteins which are responsible for the diabetes related complications (15).…”
Section: Introductionmentioning
confidence: 99%